2003
DOI: 10.1002/ffj.1184
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oils of Astrodaucus orientalis (L.) Drude leaves and seeds

Abstract: The essential oils of Astrodaucus orientalis (L.) Drude leaves and seeds growing wild in Iran were examined by GC and GC-MS. The composition of the seed oil sample was compared with that of the leaf oil. Twenty-six compounds were identified in both the leaf and the seed oil. Although the composition of the seed oil was similar to that of the leaf oil, quantitative differences in concentration of some constituents were observed. The major components of the leaf oil were fenchyl acetate (44.5%) and α-pinene (21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The predominant compounds of Astrodaucus orientalis were determined as -pinene (29.6%), pinene (21.5%) and bicyclo(3.1.0)hex-2-ene (7.6%). Mirza et al (2003) (34) reported that major components of the leaf oil were fenchyl acetate (44.5%) and α-pinene (21.6%) but the major constituents of the seed oil were myrcene (47.7%) and β-pinene (21.8%) from Iran. Present analysis results were similar with this study findings but the major constituents (myrcene and fenchyl acetate) were not detected in our samples.…”
Section: Resultsmentioning
confidence: 99%
“…The predominant compounds of Astrodaucus orientalis were determined as -pinene (29.6%), pinene (21.5%) and bicyclo(3.1.0)hex-2-ene (7.6%). Mirza et al (2003) (34) reported that major components of the leaf oil were fenchyl acetate (44.5%) and α-pinene (21.6%) but the major constituents of the seed oil were myrcene (47.7%) and β-pinene (21.8%) from Iran. Present analysis results were similar with this study findings but the major constituents (myrcene and fenchyl acetate) were not detected in our samples.…”
Section: Resultsmentioning
confidence: 99%
“…Astrodaucus orientalis (L.) Drude is a plant from the Apiaceae family (Mozaffarian, 2007) and is native to Iran, Iraq and Turkey from temperate Asia, and Ukraine and the Czech Republic from Europe (Anonymous, 2019). A. orientalis, an herbaceous, erect and glabrous plant with a pleasant odor, known as mountain carrot, is found widely in different parts of Iran, especially in fields, slopes and road sides from 350 to 2,700 m altitude (Mirza, Baher, & Dini, 2003). This aromatic plant is traditionally used as a salad, vegetable and a food additive in some parts of Iran and Turkey (Yildirim, Dursun, & Turan, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In A. orientalis the major components of the leaf essential oil were fenchyl acetate (44.5%) and α-pinene (21.6%) 3 and the major components of aerial parts essential oil were α-pinene (32.7%) and α-fenchyl acetate (14.5%), 4 which resemble the major compounds of A. persicus stem/leaves essential oil. The major components of the aerial parts essential oil of A. persicus were decanal (34.8%) dodecanal (15.5%) and dodecanol (14.3%).…”
Section: Resultsmentioning
confidence: 99%
“…The essential oil of A. orientalis of Iran was reported previously. 3,4 In addition, the essential oil of aerial parts of A. persicus has recently been reported. 5 In this paper we report on the composition of the essential oils of the root, stem/leaves and flowers/fruits of A. persicus, which have not been reported previously.…”
Section: Introductionmentioning
confidence: 99%